OPTIMASI EMBUNG SEBAGAI SUMBER AIR BAKU DESA PARAN NAPA JAE, KECAMATAN BARUMUN TENGAH - Franchitika, Rizky (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The Paran Napa Jae Reservoir in Padang Lawas Regency, North Sumatra Province, along with its operation, has experienced a buildup of sediment at the bottom of the reservoir, so it is necessary to research and study the current performance of the reservoir, especially analyzing the optimization of the reservoir. This study was carried out with reference to secondary data. Rainfall data was taken from the Sumatra River Regional Center I. Data analysis to obtain rainfall intensity was by using the Mononobe Formula and flood discharge using the Nakayasu Method Formula. The rainfall value used for the calculation of rainfall intensity is the average value of the maximum daily rainfall in 2008-2018, and the population data from 2013-2016. From the results of the calculation of the optimization of raw water needs of Paran Napa Jae Village, the number of residents in 2068 is 1812 and the results of the calculation of the mainstay discharge Q80 = 0.0737 m3/sec.